“Protect Me and I will Protect You” - Haukaa, Karine; Timmerman, Alize (Homœopathic Links, 2013)
Proving via the trituration method involves the participating homeopaths explicitly. Trituration enables the substance to disclose itself and to express all levels of interference with a person. This brings the provers to a high level of understanding of the potential healing power of the substance. Vernix caseosa is the “cheese-like” substance covering the skin of new-born babies. The trituration of Vernix caseosa revealed the main themes of this remedy; themes connected to early development of children but also to adults with health problems traceable to their childhood. Boundaries, skin, protection, and insufficient separation, striving to be oneʼs own master: these are amongst the most important themes of Vernix.
Keywords: Vernix caseosa; Sarcodes; Trituration